Unintentional injuries and falls in populations in Russia.: the Ural eye and medical study and the Ural very old study - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Gilmanshin, Timur R.; Zainullin, Rinat M.; Iakupova, Ellina M.; Panda-Jonas, Songhomitra; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Gilemzianova, Leisan I.; Khakimov, Dinar A.; Miniazeva, Liana A.; Jonas, Jost B. (Heliyon, 2024)
Background - To explore the prevalence of self-reported unintentional injuries and falls (UIFs) in medium-aged and old populations in Russia and factors associated with them. - Methods - Two population-based studies (Ural Eye and Medical Study (UEMS), Ural Very Old Study (UVOS)) were carried out urban and rural areas in Bashkortostan/Russia. They consisted of 5899 individuals (age: 40+ years) and 1526 participants (age: 85+ years), respectively. We assessed previous falls as part of an interview with standardized questions, conducted in the framework of a series medical and ophthalmological assessments. - Results - In the UEMS with 5894 individuals (age:59.0 ± 10.7 years), UIF prevalence was 1101/5894 (18.7 %; 95 % confidence interval (CI)CI:17.7,19.7), with 1,2,3,4,5,6,7,8,9, or 10+ UIFs reported by 766 (69.6 %),146 (13.3 %),56 (1.4 %),15 (1.4 %),19 (1.7 %),3 (0.3 %),2 (0.2 %),1 (0.01 %), and 10 (0.9 %) participants, respectively. The UIFs had occurred as outdoor incidents (n = 594; 53.8 %), at home (n = 162; 14.7 %), on the road or traffic accidents (n = 109; 9.9 %), at work (n = 77; 7.0 %), during garden work (n = 24; 2.2 %) or as falls from a higher level (n = 17; 1.5 %) or from house roofs (n = 16; 1.4 %). In 100 (1.7 % of the total study population; 9.1 % of the group with UIFs) participants, low vision was reported as a major cause for the UIF. Higher UIF prevalence was associated (multivariable analysis) with older age (odds ratio (OR):1.01; 95%CI:1.005,1.02;P < 0.001), urban region of habitation (OR:1.59; 95%CI:1.37,1.85;P = 0.001), higher smoking package number (OR:1.01; 95%CI:1.004,1.01;P = 0.001), longer waist circumference (OR:1.01; 95%CI:1.002,1.01;P = 0.008), higher prevalence of a history of arthritis (OR:1.38; 95%CI:1.18,1.62;P < 0.001) and backache (OR:1.73; 95%CI:1.49,2.02;P < 0.001), and higher depression score (OR:1.05; 95%CI:1.03,1.07;P < 0.001). Out of 1525 UVOS participants (age:88.8 ± 2.9 years; range:85-103.1 years), the UIF prevalence was 780/1525 (51.1 %; 95%CI: 48.6, 53.6), with 390 (50.0 %), 116 (14.8 %), 49 (6.3 %), 12 (1.5 %), 8 (1.0 %), 2 (0.3 %), 4 (0.5 %), 1 (0.1 %), and 15 (1.9 %) participants reported about 1,2,3,4,5,6,7,8,9,or 10+ UIFs, respectively. The UIFs had occurred as outdoor incidents (n = 386; 25.3 %), at home (n = 214; 14.0 %), on the road or traffic accidents (n = 22; 1.4 %), at work (n = 21; 1.4 %), during garden work (n = 10; 0.7 %) or as falls from a higher level (n = 11; 0.7 %) or from house roofs (n = 1; 0.1 %). A higher UIC prevalence correlated with female sex (OR:1.65; 95%CI:1.30,2.09;P < 0.001) and Russian ethnicity (OR:1.26; 95%CI:1.02,1.56;P = 0.03). - Conclusions - UIFs have occurred to a substantial part of the adult and very old population in Russia.